SIGNS OF PSYCHOLOGICAL STRESS IN FOREIGN LANGUAGE LEARNING AMONG STUDENTS OF PEDAGOGY AT VNU UNIVERSITY OF LANGUAGES AND INTERNATIONAL STUDIES - Lan, Dang Thi (VNU Journal of Foreign Studies; Vol 36 No 2, 2020)
Innovations in training modes, pedagogical and learning methods so as to ensure outcome standards are essential and definitely benefit all stakeholders. They, however, may cause certain difficulties to students, which can put them at risk of psychological stress (PS). Students at the University of Languages and International Studies under Vietnam National University, Hanoi (ULIS-VNU) are no exception. The study aims to reveal the levels of PS manifestation in foreign language learning activities of students of pedagogy (i.e. those majoring in foreign language teacher education) at ULIS-VNU. The results show that the PS these students suffer from stands ​at average levels. Out of the four PS manifestations, cognitive and behavioural signs are greater than physiological and emotional ones. PS levels do not significantly vary among faculties. However, students of the Faculty of Chinese Language and Culture, the Faculty of Japanese Language and Culture, the Faculty of Russian Language and Culture exhibit slightly higher levels of PS than students of the Faculty of French Language and Culture, the Faculty of Korean Language and Culture, and the Faculty of English Language Teacher Education. The findings can help these faculties develop and deliver timely supportive measures for addressing their students’ PS.